Biological therapy in pediatric age. (November 2020) - Penagini, Francesca; Cococcioni, Lucia; Pozzi, Elena; Dilillo, Dario; Rendo, Giulia; Mantegazza, Cecilia; Zuccotti, Gian Vincenzo
Graphical abstract: Abstract: Biological therapies, especially blocking tumor necrosis factor-α (TNFα) agents have radically changed the therapeutic approach and disease course of pediatric inflammatory bowel disease (IBD). In particular, drugs such as infliximab (IFX) and adalimumab (ADA) have been demonstrated to be effective in inducing and maintaining corticosteroid-free remission in both adult and pediatric patients with Crohns Disease (CD) and Ulcerative colitis (UC). Biosimilar biological (BioS) therapy is increasingly being used in pediatric age even though most knowledge on the safety and efficacy of these agents is based on IFX in adult IBD data. Studies show high rates of clinical response and remission in both IFX naïve patients and in patients switched from originator to BioS with similar risks of adverse events (AEs) as those reported with IFX originator. In the present review indications, efficacy and AEs of biological therapy in pediatric IBD will be discussed, as well as the role of other biological agents such as Golimumab, Vedolizumab and Ustekinumab, the role of BioS biological therapy and utility of therapeutic drug monitoring in clinical practice.